Micro-Progressive Punching (µPP): A New Method for Manufacturing Micro-Plate Implant - Yani Kurniawan; Dede Lia Zariatin; Dhatu Allegra Tsumu; Bambang Sulaksono (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2026)
Manufacturing of micro-plate implants using die-sinking EDM requires a processing time of about 5 hours, and there is a decrease in hardness below the raw material. To speed up the manufacturing time and prevent a decrease in material hardness, a new method is needed to manufacture micro-plate implants. This study introduces the micro-progressive punching (µPP) method to manufacture micro-plate implants. In addition, the quality of micro-plate implants such as the shape of the cutting surface and hardness produced using the µPP method were also investigated. The investigation results show that the µPP successfully made micro-plate implants with a processing time of about 10 minutes. The shape of the cutting surface has an average relatively short burr height of about 24 µm. The Hardness of the resulting micro-plate implants increased near the cutting surface with an average of about 10% of the raw material. These findings show that µPP can be employed as a substitute method for producing micro-plate implants.